2011
DOI: 10.1590/s1415-43662011000100005
|View full text |Cite
|
Sign up to set email alerts
|

Disponibilidade de zinco para milho em resposta à localização de fósforo no solo

Abstract: RESUMOA aplicação de P no solo pode afetar a disponibilidade de Zn para as plantas, dependendo de sua localização. Com o objetivo de avaliar a resposta de milho à adição de Zn no solo e determinar seu nível crítico no solo e na planta, em relação à localização de P, em amostras de dois solos de Minas Gerais, realizou-se um ensaio em casa de vegetação. O experimento consistiu em um arranjo fatorial (2 x 3 x 6), correspondendo a dois solos (Latossolo Vermelho Amarelo variação Una e Argissolo Vermelho Amarelo, do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 15 publications
1
6
1
7
Order By: Relevance
“…Tito et al [38] analyzing increasing doses of zinc in beans, also found no significant effect on the weight of the roots. However, it had a significant effect on the dry mass of stems and grains, corroborating [39] that researched about corn, and disagreeing with [40] for the cultivation of sorghum. Regarding Cr, [41] observed that the reduction in dry matter of shoots and roots of soybeans occurred at 40 mg Cr +3 L −1…”
Section: Resultssupporting
confidence: 71%
“…Tito et al [38] analyzing increasing doses of zinc in beans, also found no significant effect on the weight of the roots. However, it had a significant effect on the dry mass of stems and grains, corroborating [39] that researched about corn, and disagreeing with [40] for the cultivation of sorghum. Regarding Cr, [41] observed that the reduction in dry matter of shoots and roots of soybeans occurred at 40 mg Cr +3 L −1…”
Section: Resultssupporting
confidence: 71%
“…os maiores incrementos nas variáveis fenológicas ocorreram para 60 -75 mg de P dm -3 no substrato. a aplicação de doses crescentes de P provocou aumento linear no teor de P disponível no substrato, independentemente da adubação com zinco (Figura 1a Muner (2011), plantas bem supridas em P e zn apresentam expressivas médias de massa seca e produção. contudo, plantas adubadas com P, na ausência de aplicação de zn, demonstraram sinais de toxidez de P, em virtude do acúmulo desse nutriente no tecido e da ineficiência de utilização pela planta, o que possivelmente está relacionado ao efeito sinegístico desempenhado pelo zn.…”
Section: Resultsunclassified
“…Values increased and corresponded to 21.23 and 22.21 mg kg -1 when the dose was halved and when the dose was absent, respectively. The use of high P doses could impair the assimilation of the Zn micronutrient (MUNER et al, 2011) wherein the deficiency is relatively common mainly due to the low amount in the cerrado soils (VENDRAME et al, 2007). Table 5.…”
Section: Resultsmentioning
confidence: 99%